2013
DOI: 10.1002/nme.4525
|View full text |Cite
|
Sign up to set email alerts
|

Interval uncertain method for multibody mechanical systems using Chebyshev inclusion functions

Abstract: SUMMARYThis study proposes a new uncertain analysis method for multibody dynamics of mechanical systems based on Chebyshev inclusion functions The interval model accounts for the uncertainties in multibody mechanical systems comprising uncertain‐but‐bounded parameters, which only requires lower and upper bounds of uncertain parameters, without having to know probability distributions. A Chebyshev inclusion function based on the truncated Chebyshev series, rather than the Taylor inclusion function, is proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(84 citation statements)
references
References 43 publications
0
84
0
Order By: Relevance
“…Recently, there have been some published papers which consider the uncertainty in the analysis or optimization of multi-body systems [31][32][33][34]. The proposed method in this paper can also be extended for use in uncertain multi-body dynamics systems governed using differential algebraic equations (DAEs).…”
Section: Discussionmentioning
confidence: 90%
“…Recently, there have been some published papers which consider the uncertainty in the analysis or optimization of multi-body systems [31][32][33][34]. The proposed method in this paper can also be extended for use in uncertain multi-body dynamics systems governed using differential algebraic equations (DAEs).…”
Section: Discussionmentioning
confidence: 90%
“…Similar to the Taylor series, the Chebyshev series can also be used to expand the continuous function, with the Chebyshev polynomials to replace the power function in the Taylor expansion. Wu and et al [33,34] has shown that the Chebyshev polynomials have higher approximation accuracy than the Taylor polynomials under the same orders.…”
Section: Chebyshev Surrogate Modelmentioning
confidence: 97%
“…It can be found that under the same numerical cost which indicates the same number of terms of the Taylor expansion and Chebyshev expansion, the latter will lead to higher accuracy for most problems. A detailed comparison between the Taylor expansion and the Chebyshev expansion can be found in [33,34], which demonstrated the advantages of the Chebyshev method, including in the dynamics problems.…”
Section: Chebyshev Surrogate Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…The interval objective and constraint functions were transformed into deterministic ones by prescribing their acceptable possibility levels, and the resulting deterministic model was further transformed into an unconstrained singleobjective one by weighting and penalty function methods, which was then solved by deterministic algorithms. Wu et al (2013;2015a) proposed the high-order Taylor inclusion function to compress overestimation in interval arithmetic and utilized the Chebyshev surrogate model to approximate the highorder coefficients of the Taylor inclusion function. They further integrated the Chebyshev inclusion function and an interval bisection algorithm to avoid the inner layer optimization.…”
Section: Introductionmentioning
confidence: 99%